Stochastic Stability in Network with Decay - Francesco Feri (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper considers a simple communication network characterized by an endogenous architecture and an imperfect transmission of information. We analyze the process of network formation in a dynamic framework where self interested individuals can form or delete links and, occasionally, are doing mistakes. Then, using stochastic stability, we identify which network structures the formation process will converge to.
Keywords: A14; D20; J00; 330; Network; Decay; Strategical interaction; Soziales Netzwerk; Nash-Gleichgewicht; Spieltheorie